Effectiveness Test of Mangrove Leaf (Rhizophora Apiculata) on Decreasing Blood Glucose Levels and Pancreas Histopatology Streptozotocin Induced Male White Rats - Joni Tandi; Mohammad Fahri; Nurul Fatma; Viani Anggi; Recky Patala; Tien Wahyu Handayani (Postgraduate, University of Mataram, 2023)
Hyperglycemia, a symptom of diabetes mellitus, can lead to oxidative stress, which is indicated by elevated malondialdehyde levels. Mangrove (Rhizophora apiculata) contains secondary metabolites of alkaloids, flavonoids, saponins and tanins, this can lessen how much oxidative stress there is in DM. This study intends to demonstrate the efficacy of mangrove extracts in lowering blood glucose levels and detecting pancreatic damage. The study used 30 male Wistar rats which were divided into 6 groups (group I: normal control, group II: negative and group III: positive control given glibenclamide 0.45 mg) and the test group (trial group). group IV: level 25 mg/kg BW, group V: level 50 mg/kg BW and VI: level 75 mg/kg BW) The DM model was made by streptozotocin induction. Pancreatic damage seen at 700 magnification saw pancreatic Î² cells as well as the islets of Langerhans' endocrine cells. The results of research on ethanol from mangrove leaves at levels of 75 mg/kg BW are substances that are effective at lowering blood sugar levels, which on average were 105 mg/dL with a hazard value of 1.2. When compared with glibenclamide mangrove extract is not equivalent to glibenclamide but has lowered glucose levels.